Circulating miR-133b and miR-21: potential non-invasive diagnostic biomarkers of coronary artery disease. (25th November 2020) - Kumar, D; Narang, R; Sreenivas, V; Rastogi, V; Bhatia, J; Saluja, D; Srivastava, K
Abstract: Background: While coronary artery disease (CAD) has become a major threat worldwide, the timely biomarker-based early diagnosis of CAD remains a major unmet clinical challenge. Purpose: We aimed towards assessing the level of circulatory microRNAs as candidates of novel biomarkers in early diagnosis of CAD. Methods: A total of 147 subjects were recruited from Delhi and surrounding regions which includes 78 subjects with angiographically proven CAD, 15 pre-atherosclerotic normal coronary artery (NCA) subjects and 54 healthy individuals. Quantitative real-time PCR assays were performed using total RNA isolated from plasma of CAD patients and healthy individuals in order to measure the relative expression profiles of circulating miR-133b and miR-21. The severity level of the disease in each individual was assessed on the basis of number of diseased vessels involved and extent of stenosis. Results: MiR-133b was found to be significantly downregulated (p<0.05) by 4.6 fold whereas miR-21 was significantly upregulated (p<0.05) by ∼2 fold in plasma samples of CAD patients as compared to healthy individuals. Importantly, both the miRNAs showed an association with disease severity as miR-133b was downregulated by 8.45 fold in acute coronary syndrome (ACS), 3.38 fold in Stable angina (SA) and 2.08 fold in NCA. MiR-21 was upregulated by 2.46 fold in ACS, 1.90 fold in SA and 1.12 fold in NCA. Moreover, miR-133b could significantly differentiate subjects with ST-elevation myocardial infarction (STEMI) from Non-STEMI. Both the miRNAs exhibited a noteworthy diagnostic potential as translated through an upstanding sensitivity and specificity. MiR-133b showed an area under the curve (AUC): 0.80 with 75.6% sensitivity and 76% specificity at recommended optimal cut-off point of 14.0 whereas, miR-21 showed and AUC value of 0.79 with 72.2% sensitivity and 69.4% specificity at optimal cut-off point of 5.59 as assessed by receiver operating characteristics (ROC) curve analysis. Conclusions: The reduced expression of miR-133b and elevated expression level of miR-21 in plasma suggest their significant role in the pathophysiology as well as their implication towards the individual's susceptibility in developing CAD. Thus, we conclude that these two circulating miRNAs could be possible candidates of non-invasive biomarkers in the early prediction and diagnosis of CAD. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Department of Science and Technology, New Delhi, India; University Grant Commission (JRF/SRF Fellowship: Ref no. 22/12/2013(ii)EU-V